2015
DOI: 10.1590/0103-8478cr20150594
|View full text |Cite
|
Sign up to set email alerts
|

Quality and stability of eggs from laying hens fed with organic minerals and lycopene

Abstract: This study aimed to evaluate the effect of using lycopene and organic minerals in diets for laying hens on the egg quality and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
1
0
1
Order By: Relevance
“…De acordo com Garcia et al (2015) o aumento no percentual da gema não se torna interessante, uma vez que, com a membrana vitelínica fragilizada torna-se difícil a manipulação do ovo sem o rompimento da gema. De forma semelhante, Cruz et al (2016) observaram aumento no percentual da gema tornando-a mais plana, consequentemente piorando a qualidade interna dos ovos.…”
Section: Discussionunclassified
“…De acordo com Garcia et al (2015) o aumento no percentual da gema não se torna interessante, uma vez que, com a membrana vitelínica fragilizada torna-se difícil a manipulação do ovo sem o rompimento da gema. De forma semelhante, Cruz et al (2016) observaram aumento no percentual da gema tornando-a mais plana, consequentemente piorando a qualidade interna dos ovos.…”
Section: Discussionunclassified
“…For instance, lycopene was tested in laying hens, and it was found that after 30 days of storage at room temperature, the combined use of lycopene (800 mg/kg of diet) and minerals reduces yolk pH. At refrigerator temperature, the use of 800 mg/kg lycopene of feed stabilized the yolk color intensity during storage ( Cruz et al., 2015 ). Similarly, astaxanthin-derived H. pluvialis was found to inhibit egg weight loss and maintain yolk color during storage at 4 °C and 25 °C ( Heng et al., 2020 ).…”
Section: Functions Of Carotenoids In Eggsmentioning
confidence: 99%